2017
DOI: 10.3892/ol.2017.7042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a protein associated with the activity of cytokine‑induced killer cells

Abstract: Abstract. Cytokine-induced killer cells (CIKs) adoptive immunotherapy for efficient antitumor ability is used clinically, but details regarding the proteins associated with CIK activity remain unclear. In the current study, the cytotoxicity of CIKs on hepatoma was identified to be significantly downregulated by 1.61-fold following gentamincin treatment. Further research revealed that a differentially expressed protein (P43) was significantly downregulated by 1.22-fold using one-dimensional gel electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Previous research has identified that haptoglobin is associated with the activation of cytokine-induced killer cells (CIKs) (12), and B cells in peripheral blood mononuclear cells (PBMCs) from blood group A could be activated by HK2 cells carrying blood group B antigen (13). In the present study, the role of HP in B-cell activation was analyzed by flow cytometry, dot-ELISA and bioinformatics.…”
Section: Introductionmentioning
confidence: 86%
“…Previous research has identified that haptoglobin is associated with the activation of cytokine-induced killer cells (CIKs) (12), and B cells in peripheral blood mononuclear cells (PBMCs) from blood group A could be activated by HK2 cells carrying blood group B antigen (13). In the present study, the role of HP in B-cell activation was analyzed by flow cytometry, dot-ELISA and bioinformatics.…”
Section: Introductionmentioning
confidence: 86%